Studies on the reduction of organic load from palm oil mill effluent (POME) by bacterial strains - Jeremiah David Bala; Japareng Lalung; Norli Ismail (International Journal of Recycling of Organic Waste in Agriculture)
Introduction Palm oil mill effluent (POME) contains large quantities of organic matter in the form of total suspended solids (TSS), volatile suspended solids (VSS), total solids (TS), oil and grease (O & G) that increase biochemical oxygen demand (BOD) and chemical oxygen demand (COD) of POME if left untreated. The main aim of the present study was to investigate the ability of bacterial strains either pure (individually) or mixed (combinations), to degrade and metabolize organic load from palm oil mill effluent. Results Sequencing of the 16S rRNA of the isolates suggests that they were identified as Micrococcus luteus 101 PB, Stenotrophomonas maltophilia 102 PB, Bacillus cereus 103 PB, Providencia vermicola 104 PB, Klebsiella pneumoniae 105 PB and Bacillus subtilis 106 PB. The use of mixed cultures in the present study showed more extensive removal of organic load (COD and BOD) than pure single cultures. Mixed cultures were found to reduce the pollutant dynamically. Thus, the mixed cultures C1 (Bacillus cereus 103 PB and Bacillus subtilis 106 PB) were the most effective bacterial combination for use in biological treatment technology of POME having the highest COD and BOD reduction rate. C1 produced the highest degradative activity in reducing COD (90.64 %) and BOD (93.11 %). Conclusion The indigenous microbial isolates from POME were observed to possess potential to degrade organic components whereas the use of mixed cultures resulted in more extensive degradation of COD and BOD than pure single cultures. This suggests that mixed culture of bacteria in the present study can be used for bioremediation of environment contaminated with polluted wastewaters. This study, however, indicates the prospect of isolating indigenous microorganisms in the POME for effective biotreatment of POME.